Association of histamine with hypertension-induced cardiac remodeling and reduction of hypertrophy with the histamine-2-receptor antagonist famotidine compared with the beta-blocker metoprolol. Issue 12 (December 2018) - Potnuri, Ajay; Allakonda, Lingesh; Appavoo, Arulvelan; Saheera, Sherin; Nair, Renuka
Abstract The association of histamine with adverse cardiac remodeling in chronic pressure overload has not received much attention. A pilot study in spontaneously hypertensive rats (SHRs) indicated a reduction of left ventricular hypertrophy (LVH) with a histamine-2-receptor (H2R) antagonist (famotidine). This finding prompted a detailed investigation of temporal variation in myocardial histamine and H2R expression and the cardiovascular response to H2R antagonism compared with that of the conventional beta-blocker metoprolol. Reduction of LVH is known to reduce the risk of adverse cardiovascular events. The myocardial histamine content and H2R expression increased with age in SHRs but not in normotensive Wistar rats. The cardiovascular response to famotidine (30 mg kg−1 ) was compared with that of metoprolol (50 mg kg−1 ) in 6-month-old male SHRs treated for 60 days. The decrease in diastolic blood pressure and improvement in cardiac function induced by famotidine and metoprolol were comparable. Both treatments caused the regression of LVH as assessed from the hypertrophy index, histomorphometry, B type natriuretic peptide (BNP), pro-collagen 1, and hydroxyproline levels. Calcineurin-A expression (marker of pathological remodeling) decreased, and Peroxiredoxin-3 expression (mitochondrial antioxidant) increased in response to the treatments. The myocardial histamine levels decreased with the treatments. The age-dependent increase in myocardial histamine and H2R in the SHRs signifies their association with progressive cardiac remodeling. The regression of LVH and improvement in cardiac function by famotidine further demonstrates the role of histamine in cardiac remodeling. Hypertrophy of cultured cardiac cells upon exposure to histamine and the H2R agonist amthamine substantiates the role of histamine in cardiac remodeling. The cardiovascular response to famotidine is comparable to that of metoprolol, suggesting repurposing of H2R antagonists for the management of hypertensive heart disease.